Contactless 3D Magnetic Field Imaging For Remote Sensing Based On Hall Sensors - Fan, Hua; Zhang, Jiayi; Cen, Yuanjun; Feng, Quanyuan (Conference proceedings : Midwest Symposium on Circuits and Systems, 2020)
This paper designs a novel system, which can collect spatial magnetic field information and perform three-dimensional (3D) imaging operation by combining electromagnetic detection, sensor technology, signal processing, and microcontroller technology. The micro-system consists of Hall voltage sensor, STM32 microcontroller, stepper motor, OLED module, and driving circuits. The experimental results show that the magnetic field detection data obtained by the 3D imaging micro-system are complete and reliable, which can fully reflect the spatial vector distribution of the target magnetic field; the 3D scanning detection operates smoothly, the parameters of which are flexible and changeable; the system has stable and reliable performance and high detection efficiency, which achieves the effective detection of the magnetic field in the target area.